Dylematy współczesnego dziennikarza/dziennikarstwa – wybrane zagadnienia - Barańska, Marzena (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The speed of information transfer, the limited forms and journalistic genres used in every day practice, inadequate professional preparation, fragmentary presentation of interviewees’ opinions, superficial journalistic research before a story is filed, and widespread access to the journalistic profession have significantly affected how the professionalism of journalists is perceived. Many journalists are inspired for this line of work, seeking sensation, or creating sensational content, which increases the number of readers, listeners or viewers as the events unfold and which contributes to an increase in the audience and in the number of readers of some titles. However, the briefness of the statements presented frequently results in journalis- tic material being one-sided and lacking an in-depth approach to the issue. Under such cir- cumstances, interventionist information materials have dominated our media, limiting the readers’ opportunity to see a good documentary or read a good article. There is a shortage of teachers with real authority in journalistic circles, who are in a position to denounce abuses and demonstrate the merits of professional journalistic abilities. The aim of the paper is to indicate journalistic behaviors that raise controversies and draw attention to the dilemmas of modern journalism which diminish the value of this profession.
The dilemmas of modern journalists/journalism – selected issues
Keywords: dziennikarstwo; dziennikarz; dylematy